Assembly and phylogenetic analysis of the complete chloroplast genome sequence of Epimedium simplicifolium (Berberidaceae), an endangered species endemic to China. Issue 2 (2nd April 2020) - Yan, Fulin; Wang, Bo; He, Shunzhi; Li, Lilang; Sun, Qingwen; Wei, Shenghua
Abstract: Epimedium simplicifolium Ying is a rare and endangered species endemic to Guizhou, China. In this study, the complete chloroplast (cp) genome of E. simplicifolium was sequenced. The total cp genomes size was 158, 745 bp in length, with 38.7% of GC content, including four distinct regions: the large single-copy region (LSC, 88, 413 bp), small single-copy region (SSC, 15, 386 bp), and a pair of inverted repeat regions (IRs, each for 27, 473 bp). The whole cp genome of E. simplicifolium encoded 131 unique genes, including 86 protein-coding genes, 37 tRNA genes, and 8 rRNA genes. Phylogenetic analysis with the previously reported cp genomes showed that all the samples of Epimedium are grouped into one group, which can be easily separated from the other genera of the Berberidaceae, and the E. simplicifolium is a separate species from the rest of the Epimedium . This plastid genome is the first report for the E. simplicifolium and will be useful data for developing markers for further studies on resolving the relationship within the Berberidaceae.